Coping with Domestic Violence in India: The Role of Spirituality and Social Support - Schineanu, A.; Earnest, Jaya (Nova Science Publishers Incorporated, 2015)
Experiences of domestic violence in Indian women are a relatively common occurrence, with at least 30% of women abused by their intimate partner (husbands) on a regular basis. There is a large degree of overlap between emotional, physical and sexual violence with 1 in 10 women experiencing all three. Domestic violence is a major contributor to the mental, physical, sexual and reproductive ill health of women, with consequences extending to affect their overall health, the welfare of their children and even their economic standing. Common mental disorders such as depression and anxiety have a dose-response relationship with the severity and length of domestic violence experiences. Resilience and coping mechanisms have been found to confer protective benefits particularly on the mental health of women experiencing domestic violence. Coping strategies and behaviours have been studied extensively in Western literature and have been categorised into active and passive forms, with active coping associated with lower levels of psychological distress. In India, sociocultural factors and gender-role expectations drive Indian women into using predominantly passive coping modalities. In this chapter we provide an overview of the issue of domestic violence in India and the underlying social and cultural factors that contributes to it. We will also discuss coping strategies used by Indian women experiencing domestic violence, in particular the role of social support, spirituality and Eastern beliefs in building resilience against common mental disorders to allow women to continue living in an often unescapable and appalling situation.